On the efficiency of techniques for the reduction of impulsive noise in astronomical images. Issue 2 (23rd September 2016) - Popowicz, A.; Kurek, A. R.; Blachowicz, T.; Orlov, V.; Smolka, B.
Abstract: The impulsive noise in astronomical images originates from various sources. It develops as a result of thermal generation in pixels or the collision of cosmic rays with an image sensor, or it may be induced by high read-out voltage in an electron-multiplying CCD (EMCCD). It is usually efficiently removed by employing the dark frames or by averaging several exposures. Unfortunately, there are some circumstances when either the observed objects or positions of impulsive pixels evolve and, therefore, each image obtained has to be filtered independently. In this article we present an overview of impulsive noise filtering methods and compare their efficiency for astronomical image enhancement. The set of noise templates employed consists of dark frames obtained from CCD and EMCCD cameras working on the ground and in space. The experiments, conducted on synthetic and real images, allowed for drawing numerous conclusions about the usefulness of several filtering methods for various: (1) widths of stellar profiles, (2) signal-to-noise ratios, (3) noise distributions and (4) applied imaging techniques. The results of this evaluation are especially valuable for selecting the most efficient filtering schema in astronomical image-processing pipelines.